Relationship of Self-Efication and Organizational Culture with Nurse Behavior in the Implementation of Safe Injecting Practices in Kendari City Hospital - La Ode Alifariki; Rahmawati Rahmawati; La Rangki La Rangki; Adius Kusnan (Jurnal Keperawatan, 2019)
Infections that occur in the hospital one of which is a nosocomial infection. Injection is one of the medical methods most often used to introduce drugs or other substances into the body for medicinal or preventive purposes. The high number of officers taking unsafe injections is one of the risk factors for nosocomial infections. The purpose of this study was to analyze the relationship between self-efficacy and organizational culture with nurse behavior in the application of safe injecting practices in Kendari City Hospital. This study used observational analytic with cross sectional approach with a sample of 55 people taken by proportional random sampling using the chi square test. The results showed that there was a relationship of self-efficacy (X2hit = 10,977, p value = 0,001), organizational culture (X2hit = 18,366, p value = 0,000) with nurses' behavior in applying safe injecting practices in Kendari City Hospital. The conclusion of the study is that all independent variables (self-efficacy and organizational culture) are related to nurses' behavior in applying safe injecting practices. It is recommended that the Hospital can provide socialization about safe injections to the nurse nurses and improve organizational culture and improve the self-efficacy efforts of implementing nurses.